GUAM: WILL IT EXPAND TO CENTRAL ASIA? - TOLIPOV, Farkhad (CENTRAL ASIA AND THE CAUCASUS, 2008)
The mini-CIS (EurAsEC, ORI, the Russian-Belorussian Union, CACO, and GUAM) is a central concern among the many other conceptual and strategic issues the Commonwealth of Independent States is facing today. GUAM stands apart: it is a unique structure that has little in common with the interstate alliances; it is a post-Soviet organization in the full sense of the word. Its three dimensions post-imperial, economic, and geopolitical confirm its specific nature.